One-pot synthesis of enhanced fluorescent copper nanoclusters encapsulated in metal–organic frameworks. Issue 40 (20th June 2018) - Han, Bingyan; Hu, Xixi; Yu, Mingbo; Peng, Tingting; Li, Ying; He, Gaohong
Abstract : The encapsulation of Cu nanoclusters (Cu NCs) in metal–organic frameworks (MOFs) would improve the properties of Cu NCs. Abstract : The encapsulation of Cu nanoclusters (Cu NCs) in metal–organic frameworks (MOFs) would improve the properties of Cu NCs. So far, these composites were reported by a two-step synthesis process. In this work, a facile one-pot synthesis of hybridization of glutathione (GSH) protected Cu NCs (Cu NCs@GSH) and MOF-5 (Cu NCs@GSH/MOFs) composites was reported for the first time. The results of UV-vis, TEM, XPS and SEM proved Cu NCs@GSH were distributed homogeneously over the entire MOF structure. The fluorescence intensity of Cu NCs encapsulated in MOF-5 was enhanced about 35-fold owing to the confining scaffold of the MOF and the stability was extended from 3 days to 3 months. Cu NCs@GSH/MOFs composites exhibited strong orange fluorescence and the emissions could change between blue, orange and red as they were partially reversible in different pH environments. This one-pot synthetic strategy could be extended for the encapsulation of fluorescent Ag NCs in MOFs as well. As-prepared Cu NCs@GSH/MOF-5 composites had high stability, and were easily recycled by centrifugation in aqueous solution, therefore, it would be utilized to develop a reusable sensor for detection of metal ions in the future.